THE RELIGION-BASED KAHOOT GAME LEARNING APPROACH WITH PAKEM STRATEGY TO IMPROVE STUDENTS LEARNING MOTIVATION AND LEARNING OUTCOMES IN EXCRETION SYSTEM TOPIC (Journal Intellectual Sufism Research (JISR), 2024)
The purpose of this research is to determine the application, effect and development of the religion-based Kahoot game on students before and after learning in improving student learning motivation and learning outcomes with the PAKEM strategy on the excretory system topic. PAKEM is an abbreviation of Pembelajaran (teaching - learning), Aktif (Active), Kreatif (Creative), Efektif (Effective) and Menyenangkan (Pleasant). This research was designed using a type of Classroom Action Research (CAR) that uses a mixed method of quantitative and qualitative methods. While the data collection technique uses pre-test and post-test questions along with a motivation survey, the analysis technique was used paired sample T-test supported by IMB SPSS software to measure learning outcomes. The students’ motivation surveys of this research was conducted at Public Junior High School of Klampis, specifically in VIII-C class, for 2 semesters with a total of 27 students, and the research topic was related to the excretion system. As for the research results, the results of the motivation survey before and after the implementation of the religion-based Kahoot game in cycle II were 63.20% and 69.60%, while the percentage results were still very different at 6.4%, and the Kahoot game was still below 70%. Therefore, in cycle I, reflection was needed to look at the shortcomings or strengths of the learning process. The results of this reflection, it was analyzed, evaluated, and implemented in cycle II. It can be said that the results of the motivation survey created by the students in the cycle increased because I and II were both classified as high. The difference between the average scores after learning in the cycles was 5.59%. Meanwhile, the percentage also increased in the Kahoot game, where the percentage of more than 4 groups exceeded 70%. The conclusion of this research is that the implementation of the religion-based Kahoot game with the PAKEM strategy can improve students’ learning motivation and learning outcomes, as evidenced by changes in average results as well as the percentage value of surveys completed by students. Apart from this, students were more active and enthusiastic when applying game-based learning from Cycle I to Cycle II.Keywords: Kahoot game, PAKEM strategy, motivation and students’ learning outcomes